2012
DOI: 10.1007/s10826-012-9617-x
|View full text |Cite
|
Sign up to set email alerts
|

Links Between Perception of Parental Actions and Prosocial Behavior in Early Adolescence

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Science+Business Media, LLC. This e-offprint is for personal use only and shall not be selfarchived in electronic repositories. If you wish to self-archive your work, please use the accepted author's version for posting to your own website or your institution's repository. You may further deposit the accepted author's version on a funder's repository at a funder's request, provided it is not made publicly available until 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 34 publications
5
21
0
7
Order By: Relevance
“…Regarding the relationship between the parenting styles of the father and mother and prosocial behavior and aggression at different moments during adolescence (Mestre et al, 2007; Richaud et al, 2013), the findings resemble those for the relationship between peer attachment and prosocial behavior. Adolescents that perceived support and communication from their father and mother behaved more prosocially 1 year later.…”
Section: Discussionmentioning
confidence: 67%
“…Regarding the relationship between the parenting styles of the father and mother and prosocial behavior and aggression at different moments during adolescence (Mestre et al, 2007; Richaud et al, 2013), the findings resemble those for the relationship between peer attachment and prosocial behavior. Adolescents that perceived support and communication from their father and mother behaved more prosocially 1 year later.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have shown the prominent roles that relational variables (e.g., parental relationship, parental styles, and parental practices) play in the promotion of prosocial behavior. Specifically, cross-sectional and longitudinal studies have shown that parents who are more authoritative in their parenting style (Hastings, Zahn-Waxler, Robinson, Usher, & Bridges, 2000), express more warmth and support and use positive parental practices have more prosocial children (Carlo, MacGinley, Hayes, Batenhorst, & Wilkinson, 2007;Richaud, Mesurado, & Lemos, 2013). Baumrind (1966Baumrind ( , 1996 defined the authoritative parental style as a combination of high levels of demandingness (or control) and responsiveness (or warmth) with their children.…”
Section: Parental Variables and Prosocial Behaviormentioning
confidence: 99%
“…A modo de ejemplo, se sabe que, en población infantil, la dimensión respuesta está asociada al incremento en la cantidad de vocabulario, mejores habilidades sociales y menor agresividad, mayor autorregulación y mayor desarrollo prosocial y al mayor uso del afrontamiento aproximativo en niños (Farrant & Zubrick, 2011;Gaylord-Harden, Campbell, & Kesselring, 2010;Jennings et al 2008;Kaiser, McBurnett, & Pfiffner, 2011;Richaud de Minzi, 2010;Valiente, Lemery-Chalfant, & Swanson, 2009). En adolescentes, se encuentra relacionada con un mayor ajuste psicológico, mayor autoestima y menos síntomas depresivos, menor consumo de alcohol y drogas, mayor satisfacción con la vida, mayor resolución de conflictos y menor agresividad hacia los pares (Behnke, Plunkett, Sands, & Bámaca-Colbert, 2011;Brody et al, 2009;Clark, Belgrave, & Abell, 2012;Dwairy & Dor, 2009;Kokkinos & Voulgaridou, 2016;Lee, 2011;Missotten, Luyckx, Van Leeuwen, Klimstra, & Branje, 2016;Ozer, Flores, Tschann, & Pasch, 2011;Richaud de Minzi, Lemos, & Mesurado, 2011;Richaud de Minzi, Mesurado, & Lemos, 2012;Rohner, 2010;Rohner, Khaleque, Elias & Sultana, 2010;Schwarz et al, 2011); y menos conductas externalizantes y mayor estabilidad emocional, menos síntomas paranoides, mejor ajuste psicológico, menor ansiedad, menor uso de pensamiento dialéctico, menor cantidad de signos de trastornos de personalidad y mayor uso de afrontamientos de tipo aproximativos en adultos (Chyung & Lee, 2008;de la Iglesia, 2013;Khaleque & Rohner, 2012;Mehrad Sadr, 2016;Riggio, 2004;Riggio & Kwong, 2011;Ripoll-Nuñez & Álvarez, 2008;Xu et al, 2016).…”
Section: Parentalidad Y Variables Asociadasunclassified